Ecologia populacional em jaboticabais no sudoeste do Paraná - Moura, Amanda Pacheco Cardoso (2020)
In the Southwest of Paraná, several forest fragments of Mixed Ombrophylous Forestwere identified, with a high density of jaboticabeira (Plinia cf peruviana), named asjaboticabais. In these places there is extractive harvest of fruits (jaboticabas) andother anthropic actions, that can alter the natural regeneration of the species. Weaimed with this work verify population ecology in jaboticaba trees through studies onvegetative and reproductive phenology, diameter growth of jaboticaba trees andregeneration dynamics. We observed the vegetative and reproductive phenology of15 jaboticaba trees in three municipalities (CL, PB and VT) during three years. Fromthe dendrochronology, we evaluated the diametric increment and adjusted growthequations for adult jaboticaba trees in CH, CL, PB and VT. We delimit sample units inCL, PB and VT to analyse regeneration, and calculate the diametric distribution,density, mortality and parameters for growth, survival and elasticity using IntegralProjection Model (IPM). In these places we also observed the amount of fruitsremaining after extractive harvest. The total duration of the cycle was differentbetween sites, and CL had longer duration (120 days) of reproductive phenophases,which was associated with lower mean temperature of the site. Temperature andphotoperiod were the best predictor variables for young leaf and flower bud. The timeseries reached periods of ~ 120 years in CH, PB and VT and ~ 75 years in CL.Chapman-Richards model showed better adherence to the time series individually ateach location, while Monomolecular model better represented the total data set forthe species. For the first time we demonstrated the growth and age of jaboticabatrees by dendrochronology. The results allow to estimate establishment ofjaboticabais in the region and to define strategies of management and conservationof the species. We first recorded the fusion of logs for species of the genus Plinia,verified by the double marrow found in the samples. The regeneration showed highdensity of individuals of the smallest size classes, but gaps between individuals ofintermediate size, result of the history of anthropic actions of the sites. The finitepopulation growth rate (λ) for the total collection interval, indicated that the threestudied jaboticabais have stable populations with little growth. The highest probabilityof mortality occurred in the smallest individuals (<0.3 m of height), and the results ofelasticity showed that survival is the main factor to be considered in the conservationof the species. The number of fruits remaining after harvest was considered sufficientfor regeneration. From these results we suggest conservation actions forjaboticabais, such as removing grazing from cattle and avoid cut of regeneratingvegetation at harvest time, in order to preserve the regenerating jaboticabeiras andensure recruitment between size classes.